IMPLEMENTATION OF E-PERFORMANCE AS A SYSTEM FOR ASSESSING THE WORK ACHIEVEMENT OF THE STATE CIVIL APPARATUS IN THE REGIONAL PERSONNEL AGENCY OF LAMONGAN REGENCY - Monica Maulidian Pratiwi; Eko Priyo Purnomo; Tengku Imam Syarifuddin (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2021)
The application of e-performance in the Lamongan Regency Government is to improve the performance of ASN, which initially did not have a good performance monitoring system. The implementation of e-performance involves all OPD in Lamongan Regency. The application of e-performance at the Lamongan Regency Regional Personnel Agency is supported by a legal basis, namely Regent Regulation Number 20 of 2019 concerning the provision of Additional Income Improvement (TPP) to Civil Servants in the Lamongan Regency Government. , this system is monitored directly by the superiors of each ASN, e-performance assessment is able to have a positive impact on ASN performance.